The Limestone-Granite Contact-Deposits of Washington Camp, Arizona - W. O. Crosby (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
WASHINGTON CAMP, in Santa Cruz county, Arizona, is a small and little known mining district situated on the lower, eastern slope of the Patagonia mountains, about 20 miles east of Nogales and a like distance south of Patagonia Station on the Sonora railroad, which connects it Benson, 83 miles from Nogales, with the main line of the Southern Pacific. This district is also about 4 miles north of the international boundary, 35 miles west of Bisbee and 40 miles north of Cananea, in Sonora. The topography of the district, which lies at a general elevation of 5,500 ft. above the sea, is only very moderately rugged, and presents no obstacles to mining operations. Although some of the claims of the camp, including the Pride of the West, Belmont and Holland, were extensively worked for silver 25 years ago, they passed, at moderate depths, as in so many other districts, out of the argentiferous lead carbonate and sulphide into zinc, copper and iron sulphides; and for two decades the camp was abandoned and almost forgotten. In recent years, however, its apparent possi¬bilities as a copper producer have led to a revival of mining activity; but not, as yet, with conspicuous success. Although economically relatively unimportant, the deposits of Washington Camp are, mineralogically and structurally, nevertheless, typical examples of ore-bodies developed in connection with the garnet ledge now recognized as a normal feature of granite-limestone contacts; and, in the opinion of the writer, this is an instance where a minor example is yet essentially normal and capable of throwing important light upon the origin and genetic relations of the type.